Membangun Fondasi Emas: Analisis Komprehensif Perkembangan dan Mekanisme Perilaku Anak Usia Dini dalam Era Digital - Sutra Awaliyah Darfin; Nurhalisa Fitriani Ahsan; Putry Lestari Rahmat; Nabila Nur Afifah; Ulfi Mutmainna Sari; Trisuratma Yulia Permata (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research comprehensively examines the development and behavioral mechanisms of early childhood in the context of the digital era, with a particular focus on the interaction between technology use and the formation of fundamental social-emotional skills. Using a mixed-method approach with a sample of 180 children aged 3-6 years from various socio-economic backgrounds in Bulukumba, this research reveals the complexity of the relationship between digital exposure, parenting patterns and child development. Results show that the balance between digital and conventional interactions has a significant impact on children's social-emotional development, with the degree of influence varying based on demographic factors and parenting patterns. This research makes an important contribution to understanding the mechanisms that shape children's behavior in the digital era and its implications for parenting and educational practices.